Generalized annular lichen planus: an atypical case - Gutierrez Luza, Shady Helen (2025)
Lichen planus is a chronic, inflammatory, autoimmune disease that affects the skin, mucousmembranes, and nails. Although its exact cause remains unknown, it has been associated withhepatitis C, bacterial infections, metal allergens, medications, and emotional stress. It has alsobeen linked to conditions such as psoriasis, diabetes, hypertension, and thyroid disorders. There are several variants of lichen planus, among which, annular lichen planus presents with an unusualand more uncommon distribution pattern. It is characterized by polygonal, purple, pruritic lesions,as well as papules and plaques that are symmetrically and bilaterally distributed. We report a clinical case of annular lichen planus with an atypical and generalized presentation that responded favorably to treatment. The patient was a 67-year-old man who sought medical attention due to intense pruritus and a generalized dermatosis of six months’ duration. Physical examination revealed multiple annular plaques measuring 0.5 to 1.5 cm, with erythematous,raised borders and atrophic centers, located on the trunk, neck, groin, and face. Dermoscopyshowed Wickham’s striae and brown globules in the depressed centers. Laboratory results werenormal, and serologic tests for hepatitis B and C, and HIV were negative. The definitive diagnosiswas disseminated annular lichen planus, confirmed by skin biopsy. Treatment consisted of topicalcorticosteroids, which led to favorable clinical progress, including resolution of lesions and reliefof pruritus. This case underscores the importance of recognizing atypical variants, as appropriate diagnosis and treatment can result in excellent outcomes, even in extensive and rare presentations.